Immigration from the Immigrants’ Perspective: Analyzing Survey Data Collected among Immigrants and Host Society Members - Ramos, Alice (2019)
Immigration has been one of the most crucial global phenomena, changing the fabric of many societies, and a topic of substantial research. Much of this research has focused on how the host society views immigrants and immigration, or on the societal factors influencing the latter. The goal of this thematic issue is to present different studies focusing on various aspects of immigration from a perspective that has not been often viewed under the magnifying glass so far, but which is of major importance: looking at immigration from the immigrants’ point of view.